An investigation into the changing constructs of Psychological Immunity in Academic context Amidst COVID-19 - et. al., Tanveer Kaur, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Background: The present research has been initiated in the backdrop of Covid-19 Pandemic and henceforth, acknowledges the psychological impact of the disease followed by global lockdown on human lives. The study analyzes the challenges faced by academic fraternity i.e., teachers, students, and policy makers, owing to complete lockdown of educational machinery, introduction of digital learning and changing skillset of teachers and students in the new normal. Methods: The present research work has been conducted following the approach of extensive narrative analysis during the period of March 2020 to Aug 2020 , in order to understand the changing psychological constructs for teachers and students to cope with evolving educational transformations , post complete lockdown of educational institutions. Results: Initial understanding of the existing dimensions of educational psychology confirm that psychological interventions have been largely confined to conventional physical classroom scenarios. Since the lockdown has shaken this prime setting and given rise to a naïve concept of virtual classroom, the present study invokes the idea of readjusting the constructs of educational psychology to cope with the evolving dimensions of online classroom learning around the globe. The study further provides a framework for understanding the key factors that determine the psychological immunity among teachers and students, which have been redefined. Conclusions: The study concludes that redefined dimensions of Self Identity , Academic resilience , Adaptability and Emotional Intelligence emerged as strong contributors to the concept of psychological immunity of teachers, which are found crucial in dealing with the ongoing global disruption of education during the pandemic. Based on these findings, researchers further offer psychological interventions necessary for coping and embracing the digital upheavals in academic sector. The study further presents a rich figurative analysis of redefined psychological immunity constructs, using the Psychological Immunisation Process of Self Organisation (Hiver, 2015) which replicates the current psychological well- being of academic stakeholders in the wake of COVID-19.